Visualize Dynamics of Chromosome Structure Formation and DNA Repair/Recombination Coupled With DNA Replication: Tight Coupled Role of DNA Replication in Chromosome Compaction and DNA Recombination - Gotoh, Eisuke (IntechOpen, 2011)
None